Does Leverage, Dividend Per Share, and Cash Flow Volatility Affect Hedging Decisions?: An Empirical Study on Listed Manufacturing Companies - Nikke Yusnita Mahardini; Neneng Sri Suprihatin; Fanny Nurzamzami (Universitas Padjadjaran, 2020)
The purpose of this study is to examine the effect of leverage, dividend per share, cash flow volatility on the hedging decision. This study uses secondary data of financial statements or annual reports published in the Indonesia Stock Exchange (IDX). The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2015-2018. Purposive sampling technique is adopted in determining the sample of the study. Fourteen listed manufacturing companies are involved in this study. The method of data analysis used is the logistic regression method. The results of the study indicate that leverage and dividend per share have a significant effect on hedging decisions. Meanwhile, Cash flow volatility has no significant effect on hedging decisions.